On the question of literary research of schoolchildren - Chjen Elena Vitalievna; Murodillayeva Mohidil (Zien Journals, 2022)
The article examines the history of the issue and the actual problems of literary research in the process of school study of Russian literature.
Keywords: Research; research activity; development of spirituality; the nature of human thinking